Crosstalk Among YAP, LncRNA, and Tumor-Associated Macrophages in Tumorigenesis Development - Xu, Jing; Liu, Xin-Yuan; Zhang, Qi; Liu, Hua; Zhang, Peng; Tian, Zi-Bin; Zhang, Cui-Ping; Li, Xiao-Yu (Frontiers in Oncology, 2022)
Long non-coding RNAs (ncRNAs), which do not encode proteins, regulate cell proliferation, tumor angiogenesis, and metastasis and are closely associated with the development, progression, and metastasis of many cancers. Tumor-associated macrophages (TAMs) in the tumor microenvironment play an important role in cancer progression. The Hippo signaling pathway regulates cell proliferation and apoptosis, maintains tissue and organ size, and homeostasis of the internal environment of organisms. Abnormal expression of the Hippo signaling pathway components widely observed in various malignancies. Further, TAM, lncRNA, and YAP are currently valuable targets for cancer immunotherapy. In this review, we have logically summarized recent studies, clarified the close association between the three factors and tumorigenesis, and analyzed the outlook of tumor immunotherapy.